Winners take all the elite charade of changing the world - Giridharadas, Anand (New York Alfred A. Knopf, 2018)
Anand Giridharadas takes us into the inner sanctums of a new gilded age, where the rich and powerful fight for equality and justice any way they can?except ways that threaten the social order and their position atop it. They rebrand themselves as saviors of the poor; they lavishly reward ?thought leaders? who redefine ?change? in ways that preserve the status quo; and they constantly seek to do more good, but never less harm.
Includes bibliographical references (pages 271-276) and index.
Keywords: Social change--United States